Impact of Reverse Logistics in the Malaysian Electrical and Electronics Industry - Prashanth Beleya; Mahendra Chelliah; Mohd Abidin Abu Bakar (International Journal of Supply Chain Management, 2017)
In todays world, technology keep on evolving at a fast pace. The revolution of technology can be witnessed since the past couple of decades. This leaded to the rapid growth of the EE industry as the dependence of human on electronic products increased rapidly over the years. In Malaysia, Electrical and Electronic industry plays a leading role in the manufacturing sector by contributing 26.94% of manufacturing output, 48.7% of export and 32.5% of employments [33]. There are approximately 1,900 companies active in this industry spread across a diverse range of sub-sectors such as consumer electronics, electronic components, industrial electronics and electrical product. The rapid expansion of EE industry and the rapid continuous innovation of state of art technology accelerated the EE product to be outdated at a short leading to significant increase in e-waste which consists of materials that are no longer usable which come from a range of electronics, from computers to household appliances to cell-phones [28]. This phenomenon is worsening many factors such as increasing population growth, increasing in purchasing power, affordability contributes to the generation of e-waste. Furthermore, in this era of advancing technologies, EE products have become a vital need in every segment of the society from a person to business entities and industry. However, the current RL in Malaysian EE is still low and not able to help in the reduction of all this e-waste. Besides the issue of e-waste, Malaysian EE is also facing a growing demand of customer in many aspects. As the development technology is always one step ahead of the EE Companys strategy, many companies should struggle to reach to all the changes appropriately. These companies should strive to balance their operation strategy, concept of product development with volatile customer demand to achieve revenue growth. RL is a logistic is an inverse of normal supply chain activity. It focuses primarily on the return or take-back products and material from the point of consumption to the forward supply chain for recycling, reuse, remanufacturer, repair, refurbishing, or safe disposal of the product and materials [66]. By adopting RL, e-waste can be dispose in a proper way or being reuse. RL can be implements in supply chain of every industry, yet this paper will focus on the EE industry.